Analysis of the current state of national mobile games markets - Bobrov, V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2022)
The work includes a general analysis of the global market of mobile games and a comparative analysis of the largest national markets of mobile games. The key indicators of the mobile games market in different countries of the world were chosen as the object of the study. Since the beginning of the 2010s, the market has been growing steadily by 10% every year and has trends for further development. Such a process has many prerequisites: the development of mobile technologies, the improvement of the standard of living of the population, the increase of free time and the popularization of interactive entertainment. The work offers a brief description of the formation of the mobile game market and its advantages among competitors, a full description of the global mobile game market and its segregation into the largest centers and promising markets. The characteristics of the largest world markets: China, the USA, Japan, South Korea, the reasons for their success and current statistics are given. The most promising world regions are singled out: Europe, Africa and South America, and the main challenges for each of them are given. The findings provide numerical figures for developed and developing regions and the reasons why this difference exists. The graphs of the number of mobile game applications in the App Store, the number of players by region of the world, the dynamics of the market volume and the forecast for China and the USA were constructed and analyzed. Comparative tables and separated data for each of the considered regions were built. The results of the study showed that the main global markets have a common trend of growth in both the number of players and the revenue per player. In addition, the main challenge of the future can be considered approaching the maximum number of players and the limitation of their free time. Another important trend is the constant rapid development of technologies, which makes mobile games a real competitor for computer and console counterparts. The results of the research can be used to make decisions for mobile companies about entering new markets, as well as to analyze the key development trends for the coming years for the entertainment industry as a whole.